Legal protection of minority shareholders in Iran and Malaysia - Eshghi, Mohammad Reza (2016)
Minority shareholders today have an important role in the mobilization of savings, financial growth, and economic development of each country. Hence, enhanced minority shareholder protection is important, as it is associated with higher valuation of corporate assets and with more developed capital markets. As such, the rights of minority shareholders, i.e. the right to seek information, the right to voice an opinion and the right to seek redress are not fully protected be that in Malaysia or Iran. In fact, the law grants majority shareholders a widespread control over company that is capable of causing abuse and injustice towards minority shareholders. The general objective of this study is to formulate acceptable standards of minority shareholder’s protection and to ascertain the current position of minority shareholders in both countries. Subsequently, the adequacy of the existing legal framework and its enforcement to protect three basic rights of minority shareholders have been investigated by using qualitative, doctrinal, theoretical and functional legal methods. Through these methods, the study gives a sufficient accurate explanation on the relevant issues in each jurisdiction and addresses the related issues effectively to fulfil the social needs. The findings of this study acknowledge that Malaysia has attempted to enhance the minority shareholder protection in the transformation program in achieving equality in corporate ownership, good governance and sustainable business development after the 1997 Asian crisis whilst Iran has little attended to achieve the mission. However, the current provisions of company law in both countries have not completely overcome the conflict of interest between majority- minority shareholders because the focus is on director/ shareholder conflict of interests. There is still much room for company law reform in Malaysia and Iran in this area.